Algorithmic warfare and the reinvention of accuracy. Issue 2 (3rd May 2020) - Suchman, Lucy
ABSTRACT: This article aims to integrate two interrelated strands in critical security studies. The first is mounting evidence for the fallacy of claims for precision and accuracy in the United States 'counterterrorism' programme, particularly as it involves expanding aerial surveillance in support of operations of extrajudicial assasination. The second line of critical analysis concerns growing investment in the further automation of these operations, more specifically in the form of the US Department of Defense Algorithmic Warfare Cross-Functional Team, or Project Maven. Building upon generative intersections of critical security studies and science and technology studies (STS), I argue that the promotion of automated data analysis under the sign of artificial intelligence can only serve to exacerbate military operations that are at once discriminatory and indiscriminate in their targeting, while remaining politically and legally unaccountable.